The Implementation of CulturallyIResponsiveITeaching (CRT) Learning Model to Increase the Interest in Learning History of Students in Class XI Accounting at SMK Telkom Pekanbaru - Sony Setiawan; Isjoni Isjoni; Asril Asril (STKIP Taman Siswa Bima, 2025)
ThisIresearch was motivated by the lowIinterest of students in learning history subjects in class XI SMK Telkom Pekanbaru. Based on these problems, this researchIaims to determine teacher activities,Istudent activities, and student interest in learning after implementing the Culturally Responsive Teaching (CRT) learning model for class XI Accounting at SMK Telkom Pekanbaru. The research method used is ClassroomIAction Research (PTK) and the instrument used is the Teaching Module. The results of this studyIconcluded that, in cycle I, teacher activity obtained an average score of 54.25% with fairly good criteriaIand increased in cycle II by obtaining an average score of 91% with very good criteria. Student activity in cycle I obtainedIan average score of 38.5% with low criteria and increasedIin cycle II by obtaining an average score of 82% with very good criteria. While students' interest in learning history in cycle I obtained an average score of 56.33% with fairly good criteria (not yet successful) and increased in cycle II by obtaining an average score of 85% with very goodIcriteria (successful). BasedIon the research results, the CulturallyIResponsive Teaching (CRT) learning model canIincreaseIthe interest in learning history of students in class XI Accounting at SMK Telkom Pekanbaru.